1997
DOI: 10.1001/jama.1997.03540410058031
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Supplementation and In Vivo Immune Response in Healthy Elderly Subjects

Abstract: Our results indicate that a level of vitamin E greater than currently recommended enhances certain clinically relevant in vivo indexes of T-cell-mediated function in healthy elderly persons. No adverse effects were observed with vitamin E supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
154
2
5

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 444 publications
(167 citation statements)
references
References 29 publications
6
154
2
5
Order By: Relevance
“…The age-related decline in some of the T cell immune parameters such as proliferative response and IL-2 production has been contributed to the age-associated increase in macrophage PGE 2 production resulting from increased cyclooxygenase 2 activity in the old mice (15,46). The effect of supplemental vitamin E on lowering macrophage PGE 2 production and the resulting enhancement of cell-mediated immunity have previously been described both for mice and for human subjects (15)(16)(17)46). However, other effects of supplemental vitamin E on T cell immunity that may not involve PGE 2 have been suggested (17).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The age-related decline in some of the T cell immune parameters such as proliferative response and IL-2 production has been contributed to the age-associated increase in macrophage PGE 2 production resulting from increased cyclooxygenase 2 activity in the old mice (15,46). The effect of supplemental vitamin E on lowering macrophage PGE 2 production and the resulting enhancement of cell-mediated immunity have previously been described both for mice and for human subjects (15)(16)(17)46). However, other effects of supplemental vitamin E on T cell immunity that may not involve PGE 2 have been suggested (17).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, measures of cell-mediated immune function, such as delayed-type hypersensitivity (DTH) response, in vitro T cell proliferation and IL-2 production in response to the T cell mitogen Con A were increased compared with those fed 30 ppm (an adequate dietary level) of vitamin E. A dietary supplement of 800 mg of vitamin E for 30 days to men and woman over 60 years of age, increased DTH, mitogenic response to Con A, and the production of IL-2 (15). A subsequent randomized double-blind, placebo-controlled trial by Meydani et al (16) found that vitamin E supplementation improved DTH response in a group of healthy elderly subjects. In addition, Ab titer against T cell-dependent hepatitis B vaccine was significantly increased in subjects receiving supplemental vitamin E. Previous studies from our laboratory show that vitamin E exerts its effect in part by reducing macrophage PGE 2 production (14,17).…”
mentioning
confidence: 99%
“…The vitamin E levels were selected based on our previous studies in which 500 ppm vitamin E was shown to significantly improve T cell-mediated function in old mice (4,7). In addition, this is the level of vitamin E that results in similar fold increases (2-to 2.7-fold) in blood ␣-tocopherol levels of mice compared with those observed in humans following consumption of 200 -800 mg/day for a short period of time (4,10,11). All animal procedures were approved by the HNRCA Animal Care and Use Committee.…”
Section: Animals and Dietsmentioning
confidence: 99%
“…Other components of the capsules include fucoidans 12,13) , vitamin E [14][15][16] , zinc 17,18) , vitamin B6 and coenzyme Q10 19) . These supplements have been used in traditional Chinese medicine as nutritional fortification elements and are believed to improve immune function.…”
Section: Discussionmentioning
confidence: 99%